3D printing of high-volume fly ash mixtures for digital concrete construction - Panda, Biranchi (2019)
Digital concrete construction has recently become the subject of very rapidly growing research activities all over the world. It opens a new horizon and unlimited possibilities for the concrete industry, especially in terms of geometrical flexibility, reduction of manpower and costs, increased productivity, speed of construction, and sustainability. The potential of digital production of concrete is represented by exponentially increasing innovative projects and research, which are often addressed using the generalized term “3D-concrete-printing”. Recent advances in concrete printing have mainly focused on developing Portland cement (PC) based binders that are both extrudable and buildable. The production of PC is associated with many environmental challenges including the air pollution and devastation in land and resources. One of the promising measures is the development of sustainable cements, which can be achieved via two main pathways: (i) partial PC replacement with industrial by‐products and wastes and (ii) new cement formulations based on different chemistry with lower environmental impacts. This thesis is dedicated to material synthesis of two promising sustainable building materials such as (i) high volume fly ash (HVFA) cement and (ii) geopolymer based cement for extrusion-based 3D printing application.